(untitled) (Atti del Sodalizio Glottologico Milanese, 2023)
The most widespread etymology of bagaudae, the name of rebel groups in late Roman Gaul, connects it to Old Irish bág ‘fight’ and to the IE root *bhē/ōgh- (IEW 115). There are, however, phonetic problems. The historical sources and the current historiographic research do not support an original meaning such as ‘fighters’. A morphological and semantic analysis (doubts about a suffix *-aud-, the connotations associated with the term bagaudae, its use in anthroponymy etc.) points to an old dithematic compound meaning ‘collector of goods (to be allotted)’ (cf. IEW 107 *bhag-; 75 *au(dh)-).